2014
DOI: 10.1111/hpb.12125
|View full text |Cite
|
Sign up to set email alerts
|

National trends in pancreaticoduodenal trauma: interventions and outcomes

Abstract: The utilization of operations for PDT has declined without affecting mortality, but operative morbidity increased significantly over the 12 years to 2009. The development of an evidence-based approach to invasive manoeuvres and an early multidisciplinary approach involving pancreatic surgeons may improve outcomes in patients with these morbid injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 16 publications
2
44
0
1
Order By: Relevance
“…While historical data demonstrate improved outcomes compared to adult pancreatic trauma, with morbidity and mortality rates of 50% and >10%, respectively [17], these injuries remain serious. Given the large sample size, contemporary cohort, and national generalizability, the current report provides reliable estimates of morbidity and mortality at 26.5% and 5.3%, respectively, which can be used as a reference for clinician and family member expectations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While historical data demonstrate improved outcomes compared to adult pancreatic trauma, with morbidity and mortality rates of 50% and >10%, respectively [17], these injuries remain serious. Given the large sample size, contemporary cohort, and national generalizability, the current report provides reliable estimates of morbidity and mortality at 26.5% and 5.3%, respectively, which can be used as a reference for clinician and family member expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in adults have demonstrated a trend towards nonoperative strategies for these injuries [17], and numerous groups have emphasized nonoperative management even in cases of complete pancreas transection [1820]. More recently, several authors have advocated earlier surgical intervention for cases of ductal injury [4,6,21], and the introduction of laparoscopic management in pancreas trauma may impact the risk–benefit ratio for these children [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Other available scoring systems exist, 50 such as the Frey & Wardell 3 or the Lucas score 51 that take into account associated duodenal injuries, but these are rarely, if ever, used for reporting in the literature with no major series or authoritative review published over the past decade suggesting any of these scores used to assess combined pancreatoduodenal injuries. 17,30,[52][53][54][55][56][57] However, the combined grading of pancreas and duodenal injury together may have some clinical value for practical decision-making. Currently, most series describe these rare combined injuries by the OIS score for pancreas and duodenum.…”
Section: Scoring Of Injury Types and Severitymentioning
confidence: 99%
“…49 Notably, such combined injuries occur in a rare minority of patients, reported to occur in less than 8% of all children with pancreatic injury 58 and in just over 8% in all patients with pancreatic trauma. 54 As such, it is recognized that for this select patient group, the severity scoring may have less validity and precision for therapeutic decision-making. Largely, experience stems from institutional series with highvolume trauma related to penetrating mechanisms.…”
Section: Scoring Of Injury Types and Severitymentioning
confidence: 99%
“…Akefumi Sato 1) , Hirofumi Ichikawa 1) , Kazuaki Hatsugai 2) , Shigeru Ottomo 3) , Toshiaki Fukutomi 1) , Taiki Kajiwara 1) and Tetsuji Harada 1)…”
Section: Multiple Surgical Treatments Of Traumatic Pancreaticoduodenaunclassified